Method for preparing high-conductivity graphene copper composite material based on in-situ co-deposition method

Through in-situ co-deposition method and thermal evaporation technology, graphene is deposited on copper foil and stacked with hot pressing, which solves the problems of structural failure, poor conductivity and high equipment costs in the preparation of graphene copper composite materials in the prior art. The preparation of graphene copper composite materials with high conductivity was achieved.

CN119170344APending Publication Date: 2024-12-20UNIV OF SCI & TECH BEIJING

Patent Information

Application Number
CN202411254040.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

In the existing preparation methods for graphene copper composite materials, powder metallurgy is prone to destroy the graphene structure, molecular-level mixing method has poor conductivity, electrochemical deposition equipment cost is high, and high temperature in quartz tubes leads to evaporation of copper substrate, and chemical vapor deposition. The method is difficult to control the graphene content and growth time.

Method used

In situ co-deposition method is used to deposit a single layer of graphene on commercial high-purity copper foil by radio frequency plasma chemical vapor deposition, and thermally deposition copper film on the surface of graphene. The deposition process is repeated alternately and prepared in combination with stacked hot pressing technology. Highly conductive graphene copper composite material, controlling graphene content and copper film thickness to improve conductivity.

Benefits of technology

The high conductivity of graphene copper composite material is achieved, with conductivity reaching 110%-130% IACS, which avoids copper evaporation and the increase in graphene nucleation energy barrier, simplifies the process flow and reduces equipment costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170344A_ABST
    Figure CN119170344A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a high-conductivity graphene copper composite material based on an in-situ co-deposition method, relates to the technical field of preparation of copper-based composite materials, and aims to solve the problem that the conductivity is difficult to improve by an existing method for preparing the graphene copper composite material. The preparation method comprises the following steps: S1, preparing a high-conductivity graphene copper composite foil by adopting an in-situ co-deposition method; and S2, laminating and hot-pressing a plurality of high-conductivity graphene copper composite foils prepared in the step S1, so as to prepare the high-conductivity graphene copper composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of preparation of copper-based composite materials, and in particular to a method for preparing a highly conductive graphene copper composite material based on an in-situ co-deposition method. Background Art

[0002] Copper ranks second in electrical conductivity among all metals. At 20°C, copper has a conductivity of 58MS / m. It is the preferred conductive material in most electrical wiring applications and is widely used in aviation cables, rail transportation, electrical engineering, microelectronics and other fields. Therefore, even a small improvement in copper's conductivity will have a huge impact on power generation and power consumption. In addition, the conductivity of high-conductivity copper at room temperature is more than twice that of pure copper, and the weight and size of motors, transformers, generators and transmission lines will be reduced to half of the current weight. If high-conductivity copper is developed, it can significantly improve the performance of almost all electrical systems and power electronic equipment, and reduce their energy consumption, which will have huge economic and social benefits.

[0003] Traditional methods to improve the conductivity of copper materials mainly include reducing the impurity content (<10ppm) and growing single crystals to increase the conductivity of copper to 109% IACS. However, the conductivity improved by these methods is close to its theoretical limit, and new methods are urgently needed. Metal conductivity depends on carrier concentration and carrier mobility. Improving conductivity requires increasing one of these two factors without significantly reducing the other. It is well known that copper has a higher carrier concentration, while graphene (Gr) has a higher carrier mobility, about 2×10 5 cm / (Vs), the advantages of the two complement each other, so the compounding of copper and graphene is expected to achieve a significant improvement in the conductivity of copper-based composite materials.

[0004] At present, the existing methods for preparing graphene-copper composite materials are mainly to compound graphene and copper through powder metallurgy, molecular-level mixing, electrochemical deposition, chemical vapor deposition, etc., and then use vacuum hot pressing or spark plasma sintering to form a bulk material.

[0005] In the above-mentioned method for preparing graphene copper composite materials, powder metallurgy has no restrictions on the content, size, shape, etc. of copper matrix powder and reinforcement, but the mixing process easily destroys the integrity of the graphene structure and reduces the strengthening effect of graphene. Molecular mixing method can make graphene have good dispersibility in solution, and the prepared composite material has high strength, but poor conductivity. The preparation process of electrochemical deposition method is simple and controllable, and the equipment cost is low, but the problem of poor stability of graphene suspension remains to be solved. In contrast, chemical vapor deposition is the mainstream method for preparing graphene copper composite materials today. By controlling the deposition parameters, high-quality graphene reinforcement with controllable number of layers can be prepared on copper foil. The two-dimensional plane size of the graphene is large and well combined with the matrix metal, which is conducive to making the composite material obtain higher conductivity. However, in the process of chemical vapor deposition, methane is fed into the quartz tube as a carbon source for chemical reaction. The quartz tube needs to maintain a high temperature of 1000°C, and the high activation temperature will cause a large amount of evaporation of the copper substrate material, which makes the process difficult to control, may produce defects in the growing graphene, and the growth time is long. In addition, the graphene copper composite material obtained by hot pressing the foil stack obtained by depositing graphene on commercial high-purity copper foil by chemical vapor deposition and obtaining Gr / Cu / Gr foil is difficult to control because the thickness of the copper foil is fixed. Summary of the invention

[0006] The present invention proposes a method for preparing a highly conductive graphene copper composite material based on an in-situ co-deposition method, which comprises the following steps: S1: Preparation of highly conductive graphene copper composite foil by in-situ co-deposition method; S2: laminating and hot pressing a plurality of highly conductive graphene copper composite foils prepared in step S1 to prepare a highly conductive graphene copper composite material.

[0007] The present invention is further configured as follows: Step S1 includes the following steps: S1-1: In the radio frequency plasma chemical vapor deposition (RF-PECVD) system of the in-situ nano-laminated superstructure electrode material deposition equipment, a mixed atmosphere of Ar, H2 and CH4 is created. In this environment, a single layer of graphene is deposited on the surface of commercial high-purity copper foil using RF-PECVD; S1-2: transferring the copper foil on which the single-layer graphene is deposited into a thermal evaporation system, and thermally evaporating a layer of copper film on the surface of the single-layer graphene; S1-3: Repeat steps S1-1 and S1-2 alternately for multiple times to obtain a highly conductive graphene copper composite foil.

[0008] The present invention is further configured as follows: in step S1-1, the thickness of the commercial high-purity copper foil is 25 μm; the RF plasma power is 50-300 W, the growth temperature is 650-900° C., the H2 flow rate is 5-20 sccm, the CH4 flow rate is 1-5 sccm, and the growth time is 10-30 min.

[0009] The present invention is further configured as follows: the commercial high-purity copper foil used in the step S1-1 needs to be pretreated, and the commercial high-purity copper foil is ultrasonically cleaned in hydrochloric acid, acetone, and isopropanol for 5 minutes in sequence to remove organic matter and an oxide layer on its surface, and then blown dry with flowing N2; then placed in a polishing liquid, electrochemically polished for 30 minutes using a voltage of 2V, and then rinsed on its surface with deionized water for 5 minutes to wash away the polishing liquid remaining on the surface, and then blown dry with N2.

[0010] The present invention is further configured as follows: the mass fraction of the hydrochloric acid is 5%.

[0011] The present invention is further configured as follows: the polishing liquid is prepared by using phosphoric acid and ethylene glycol in a volume ratio of 3:1.

[0012] The present invention is further configured as follows: the thickness of the thermally evaporated copper film in step S1-2 is 50-200 nm.

[0013] The present invention is further configured as follows: the thickness of the highly conductive graphene copper composite foil prepared in step S1-3 is 26.2 μm.

[0014] The present invention is further configured as follows: in step S2, 16 sheets of high-conductivity graphene copper composite foil are laminated and hot-pressed; the hot-pressing pressure is 40 MPa, the hot-pressing temperature is 900° C., and the hot-pressing sintering time is 40 min.

[0015] The beneficial effects of the present invention are as follows: a single layer of graphene is deposited on a commercial high-purity copper foil by RF-PECVD, and the free radicals generated in the plasma greatly reduce the energy barrier of graphene nucleation and growth, and the overall heat budget is reduced by shortening the growth time and lowering the growth temperature, thereby avoiding the evaporation of copper. Secondly, a copper film is plated on the graphene surface by thermal evaporation to obtain a foil with a Cu / Gr / Cu layered structure. When the thickness of the foil is fixed, the graphene content in the composite material is controllably adjusted by changing the thickness of the copper-plated layer, thereby obtaining a highly conductive graphene-copper composite foil with different graphene contents. The conductivity of the graphene-copper composite material is increased by reducing the thickness of the copper-plated layer. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The process flow chart of the present invention is shown.

[0017] Figure 2The process flow chart of laminate hot pressing is shown. DETAILED DESCRIPTION

[0018] Those skilled in the art can refer to the content of this article and appropriately improve the process parameters. It is particularly important to point out that all similar replacements and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can modify or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.

[0019] Example 1

[0020] The present invention proposes a method for preparing a highly conductive graphene copper composite material by an in-situ co-deposition method, comprising the following steps:

[0021] S1: Preparation of highly conductive graphene copper composite foil by in-situ co-deposition method;

[0022] S2: laminating and hot pressing a plurality of highly conductive graphene copper composite foil sheets prepared in step S1 to prepare a highly conductive graphene copper composite material.

[0023] Wherein step S1 comprises the following steps:

[0024] S1-1: In the radio frequency plasma chemical vapor deposition (RF-PECVD) system of the in-situ nano-laminated superstructure electrode material deposition equipment, a mixed atmosphere of Ar, H2 and CH4 is created. In this environment, a single layer of graphene is deposited on the surface of commercial high-purity copper foil using RF-PECVD;

[0025] S1-2: transferring the copper foil on which the single-layer graphene is deposited into a thermal evaporation system, and thermally evaporating a layer of copper film on the surface of the single-layer graphene;

[0026] S1-3: Repeat steps S1-1 and S1-2 alternately for multiple times to obtain a highly conductive graphene copper composite foil.

[0027] The commercial high-purity copper foil in step S1-1 has a thickness of 25 μm; the RF plasma power is 50W-300W, the growth temperature is 650-900°C, the H2 flow rate is 5-20sccm, the CH4 flow rate is 1-5sccm, and the growth time is 10-30min.

[0028] The commercial high-purity copper foil used in step S1-1 needs to be pretreated, that is, the commercial high-purity copper foil is ultrasonically cleaned in hydrochloric acid, acetone and isopropanol for 5 minutes in turn to remove the organic matter and oxide layer on its surface, and then blown dry with flowing N2; then placed in the polishing liquid, electrochemically polished with a voltage of 2V for 30 minutes, and then rinsed with deionized water for 5 minutes to wash away the polishing liquid remaining on the surface, and then blown dry with N2.

[0029] The mass fraction of hydrochloric acid is 5%. The polishing liquid is prepared by phosphoric acid and ethylene glycol in a volume ratio of 3:1.

[0030] The thickness of the thermally evaporated copper film in step S1-2 is 50-200 nm.

[0031] The thickness of the highly conductive graphene copper composite foil prepared in step S1-3 is 26.2 μm.

[0032] In step S2, 16 sheets of highly conductive graphene copper composite foil are laminated and hot pressed; the hot pressing pressure is 40 MPa, the hot pressing temperature is 900° C., and the hot pressing sintering time is 40 min.

[0033] Example 2

[0034] This embodiment adopts the method of embodiment 1 to prepare a highly conductive graphene copper composite material, wherein the base material commercial high-purity copper foil is selected with a thickness of 25μm, a purity of 99.8%, and a size of 2cm×2cm. The base material is loaded on a quartz sheet with a size of 30mm×30mm×1mm. The atmosphere gas for growing graphene is a 5% volume fraction of CH4 gas diluted in high-purity H2, Ar and high-purity argon with a purity greater than 99.999%. The copper source purity for copper plating is 5N, and the copper source specification is φ6mm×6mm. The equipment adopts an in-situ nano-laminated superstructure electrode material deposition equipment and a vacuum hot pressing sintering furnace, wherein the in-situ nano-laminated superstructure electrode material deposition equipment can realize RF-PECVD growth of graphene and thermal evaporation of copper alternately. The calculation method of graphene content in graphene copper composite material adopts: (graphene volume / graphene copper composite material volume)×100%, and the thickness of a single layer of graphene is 0.34nm.

[0035] The specific steps include:

[0036] S1: Highly conductive graphene copper composite foil was prepared by in-situ co-deposition method;

[0037] Wherein step S1 comprises the following steps:

[0038] S1-1: First, commercial high-purity copper foil was selected as the substrate material, and the substrate material was pretreated, that is, 25 μm commercial high-purity copper foil was ultrasonically cleaned in 5% hydrochloric acid, acetone, and isopropanol for 5 minutes to remove the organic matter and oxide layer on its surface, and then blown dry with flowing N2. Using a 2V voltage, the substrate material was electrochemically polished in a polishing liquid prepared with phosphoric acid and ethylene glycol in a volume ratio of 3:1 for 30 minutes, and then the copper foil surface was rinsed with deionized water for 5 minutes to remove the residual polishing liquid on the surface, and then blown dry with N2.

[0039] Secondly, graphene was grown on the substrate material using RF-PECVD. The pre-treated substrate material was placed on a quartz plate and then placed in the center of the sample stage in the vacuum chamber. The vacuum chamber and each gas path were evacuated. The pressure in the vacuum chamber was pumped down to below 5 Pa using a mechanical pump. The molecular pump and each gas path valve were opened to evacuate to 10 -4 Order of magnitude. In a mixed atmosphere of 200 sccmAr and 50 sccmH2, the system is heated at 200Pa for 50min to the target temperature of 850℃, and the distance between the upper and lower plates is fixed to 2.5cm. This is a heating process and no graphene growth is performed. After reaching the target temperature, the Ar and H2 gas flows are adjusted to 50sccm and 20sccm respectively, and the system pressure is maintained at 50Pa. When the gas flow is stable, the RF power supply is turned on and the power is set to 50w for 1min of etching. Finally, 3sccm of 5% CH4 is immediately introduced for graphene growth. The growth time is 30min. After obtaining a single layer of graphene that completely covers the copper foil, the RF power supply, CH4 flowmeter, H2 flowmeter and heating power supply are turned off, and the Ar flow rate is increased to 500sccm. The temperature is quickly cooled to room temperature. After it drops to room temperature, the Ar flowmeter is turned off.

[0040] S1-2: The substrate material on which the single-layer graphene is grown in step S1-1 is transferred into the thermal evaporation chamber through the operation control system, and copper is plated on the surface of the single-layer graphene to obtain a Cu / Gr / Cu layered structure foil. First, start the mechanical pump to pump the pressure in the vacuum chamber to below 2 Pa, and turn on the molecular pump until the vacuum degree reaches 5.0×10 -4 Pa, turn on the thermal evaporation power supply, keep the evaporation current at 40-50A, and control the copper plating rate at The copper plating thickness is 200nm.

[0041] S1-1-1: The Cu / Gr / Cu composite foil after copper plating in step S1-2 is transferred into the RF-PECVD vacuum chamber through the operation control system. In a mixed atmosphere of 200sccmAr and 30sccmH2, the system is heated at 180Pa for 40min to the target temperature of 750℃, and the upper and lower plates are fixed at a spacing of 2.5cm. At this time, it is a heating process, and graphene growth is not performed. After reaching the target temperature, the Ar and H2 gas flows are adjusted to 50sccm and 10sccm respectively, and the system pressure is maintained at 30Pa. When the gas flow is stable, the RF power supply is turned on and the power is set to 100w. Finally, 5sccm of CH4 with a concentration of 5% is immediately introduced for graphene growth, and the growth time is 20min. After obtaining a single-layer graphene completely covered with a copper film, the RF power supply, CH4 flowmeter, H2 flowmeter and heating power supply are turned off, and the Ar flow rate is increased to 500sccm, and the temperature is quickly cooled to room temperature. After it drops to room temperature, the Ar flowmeter is turned off.

[0042] S1-3: Step S1-1-1 and step S1-2 are repeated alternately for six times, that is, thermal evaporation of copper and RF-PECVD on the single-layer graphene, and RF-PECVD growth of graphene on the copper-plated film are repeated alternately for six times, to obtain a graphene-copper composite foil having a thickness of about 26.2 μm and comprising six layers of copper-plated films and six layers of single-layer graphene, wherein the six layers of copper-plated films and the six layers of single-layer graphene do not contain a copper base material in a Cu / Gr / Cu layered structure.

[0043] S2: stack 16 pieces of highly conductive graphene copper composite foils prepared in step S1 and then hot press them to prepare highly conductive graphene copper composite materials. That is, stack 16 pieces of graphene copper composite foils prepared in step S1-3 and put them into the graphite mold of the hot press furnace. Set the pressure parameter to 40Mpa, the temperature parameter to 900℃, the heating and pressure increase time to 40min, and the heat preservation and pressure holding time to 40min. Turn on the mechanical pump to evacuate. When the pressure in the hot press furnace is lower than 10Pa, turn on the vacuum pump and evacuate to 1×10 -3 Pa. Turn on the heating power supply for hot pressing sintering. After the hot pressing is completed, turn off the heating power supply and cool naturally to room temperature, turn off the molecular pump and mechanical pump, open the vent valve, and open the cavity for sampling.

[0044] The CH4 is diluted with Ar.

[0045] The electrical conductivity of the graphene-copper composite was measured to be 115% IACS using the van der Pauw method.

[0046] Example 3

[0047] This embodiment adopts the method of embodiment 1 to prepare a highly conductive graphene copper composite material, wherein the base material commercial high-purity copper foil is selected with a thickness of 25μm, a purity of 99.8%, and a size of 2cm×2cm. The base material is loaded on a quartz sheet with a size of 30mm×30mm×1mm. The atmosphere gas for growing graphene is a 5% volume fraction of CH4 gas diluted in high-purity H2, Ar and high-purity argon with a purity greater than 99.999%. The copper source purity for copper plating is 5N, and the copper source specification is φ6mm×6mm. The equipment adopts an in-situ nano-laminated superstructure electrode material deposition equipment and a vacuum hot pressing sintering furnace, wherein the in-situ nano-laminated superstructure electrode material deposition equipment can realize RF-PECVD growth of graphene and thermal evaporation of copper alternately. The calculation method of graphene content in graphene copper composite material adopts: (graphene volume / graphene copper composite material volume)×100%, and the thickness of a single layer of graphene is 0.34nm.

[0048] The specific steps include:

[0049] S1: Highly conductive graphene copper composite foil was prepared by in-situ co-deposition method;

[0050] Wherein step S1 comprises the following steps:

[0051] S1-1: First, commercial high-purity copper foil was selected as the substrate material, and the substrate material was pretreated, that is, 25 μm commercial high-purity copper foil was ultrasonically cleaned in 5% hydrochloric acid, acetone, and isopropanol for 5 minutes to remove the organic matter and oxide layer on its surface, and then blown dry with flowing N2. Using a 2V voltage, the substrate material was electrochemically polished in a polishing liquid prepared with phosphoric acid and ethylene glycol in a volume ratio of 3:1 for 30 minutes, and then the copper foil surface was rinsed with deionized water for 5 minutes to remove the residual polishing liquid on the surface, and then blown dry with N2.

[0052] Secondly, graphene was grown on the substrate material using RF-PECVD. The pre-treated substrate material was placed on a quartz plate and then placed in the center of the sample stage in the vacuum chamber. The vacuum chamber and each gas path were evacuated. The pressure in the vacuum chamber was pumped down to below 5 Pa using a mechanical pump. The molecular pump and each gas path valve were opened to evacuate to 10 -4Order of magnitude. In a mixed atmosphere of 200 sccmAr and 50 sccmH2, the system is heated at 200Pa for 50min to the target temperature of 850℃, and the distance between the upper and lower plates is fixed to 2.5cm. This is a heating process and no graphene growth is performed. After reaching the target temperature, the Ar and H2 gas flows are adjusted to 50sccm and 20sccm respectively, and the system pressure is maintained at 50Pa. When the gas flow is stable, the RF power supply is turned on and the power is set to 50w for 1min of etching. Finally, 3sccm of 5% CH4 is immediately introduced for graphene growth. The growth time is 30min. After obtaining a single layer of graphene that completely covers the copper foil, the RF power supply, CH4 flowmeter, H2 flowmeter and heating power supply are turned off, and the Ar flow rate is increased to 500sccm. The temperature is quickly cooled to room temperature. After it drops to room temperature, the Ar flowmeter is turned off.

[0053] S1-2: The substrate material on which the single-layer graphene is grown in step S1-1 is transferred into the thermal evaporation chamber through the operation control system, and copper is plated on the surface of the single-layer graphene to obtain a Cu / Gr / Cu layered structure foil. First, start the mechanical pump to pump the pressure in the vacuum chamber to below 2 Pa, and turn on the molecular pump until the vacuum degree reaches 5.0×10 -4 Pa, turn on the thermal evaporation power supply, keep the evaporation current at 40-50A, and control the copper plating rate at The copper plating thickness is 100nm.

[0054] S1-1-1: The Cu / Gr / Cu composite foil after copper plating in step S1-2 is transferred into the RF-PECVD vacuum chamber through the operation control system. In a mixed atmosphere of 200sccmAr and 30sccmH2, the system is heated at 180Pa for 40min to the target temperature of 700℃, and the distance between the upper and lower plates is fixed to 2.5cm. At this time, it is a heating process, and graphene growth is not performed. After reaching the target temperature, the Ar and H2 gas flows are adjusted to 50sccm and 10sccm respectively, and the system pressure is maintained at 30Pa. When the gas flow is stable, the RF power supply is turned on and the power is set to 150W. Finally, 5sccm of CH4 with a concentration of 5% is immediately introduced for graphene growth, and the growth time is 15min. After obtaining a single-layer graphene completely covered with a copper film, the RF power supply, CH4 flowmeter, H2 flowmeter and heating power supply are turned off, and the Ar flow rate is increased to 500sccm, and the temperature is quickly cooled to room temperature. After it drops to room temperature, the Ar flowmeter is turned off.

[0055] S1-3: Step S1-1-1 and step S1-2 are repeated alternately twelve times, that is, thermal evaporation of copper and RF-PECVD are performed on the single-layer graphene, and RF-PECVD growth of graphene is performed on the copper-plated film alternately for 12 cycles, to obtain a graphene-copper composite foil having a thickness of about 26.2 μm and comprising 12 layers of copper-plated film and 12 layers of single-layer graphene, wherein the 12 layers of copper-plated film and the 12 layers of single-layer graphene do not contain a copper base material of a Cu / Gr / Cu layered structure.

[0056] S2: stack 16 pieces of highly conductive graphene copper composite foils prepared in step S1 and then hot press them to prepare highly conductive graphene copper composite materials. That is, stack 16 pieces of graphene copper composite foils prepared in step S1-3 and put them into the graphite mold of the hot press furnace. Set the pressure parameter to 40Mpa, the temperature parameter to 900℃, the heating and pressure increase time to 40min, and the heat preservation and pressure holding time to 40min. Turn on the mechanical pump to evacuate. When the pressure in the hot press furnace is lower than 10Pa, turn on the vacuum pump and evacuate to 1×10 -3 Pa. Turn on the heating power supply for hot pressing sintering. After the hot pressing is completed, turn off the heating power supply and cool naturally to room temperature, turn off the molecular pump and mechanical pump, open the vent valve, and open the cavity for sampling.

[0057] The CH4 is diluted with Ar.

[0058] The electrical conductivity of the graphene-copper composite was measured to be 121% IACS using the van der Pauw method.

[0059] Example 4

[0060] This embodiment adopts the method of embodiment 1 to prepare a highly conductive graphene copper composite material, wherein the base material commercial high-purity copper foil is selected with a thickness of 25μm, a purity of 99.8%, and a size of 2cm×2cm. The base material is loaded on a quartz sheet with a size of 30mm×30mm×1mm. The atmosphere gas for growing graphene is a 5% volume fraction of CH4 gas diluted in high-purity H2, Ar and high-purity argon with a purity greater than 99.999%. The copper source purity for copper plating is 5N, and the copper source specification is φ6mm×6mm. The equipment adopts an in-situ nano-laminated superstructure electrode material deposition equipment and a vacuum hot pressing sintering furnace, wherein the in-situ nano-laminated superstructure electrode material deposition equipment can realize RF-PECVD growth of graphene and thermal evaporation of copper alternately. The calculation method of graphene content in graphene copper composite material adopts: (graphene volume / graphene copper composite material volume)×100%, and the thickness of a single layer of graphene is 0.34nm.

[0061] The specific steps include:

[0062] S1: Highly conductive graphene copper composite foil was prepared by in-situ co-deposition method;

[0063] Wherein step S1 comprises the following steps:

[0064] S1-1: First, commercial high-purity copper foil was selected as the substrate material, and the substrate material was pretreated, that is, 25 μm commercial high-purity copper foil was ultrasonically cleaned in 5% hydrochloric acid, acetone, and isopropanol for 5 minutes to remove the organic matter and oxide layer on its surface, and then blown dry with flowing N2. Using a 2V voltage, the substrate material was electrochemically polished in a polishing liquid prepared with phosphoric acid and ethylene glycol in a volume ratio of 3:1 for 30 minutes, and then the copper foil surface was rinsed with deionized water for 5 minutes to remove the residual polishing liquid on the surface, and then blown dry with N2.

[0065] Secondly, graphene was grown on the substrate material using RF-PECVD. The pre-treated substrate material was placed on a quartz plate and then placed in the center of the sample stage in the vacuum chamber. The vacuum chamber and each gas path were evacuated. The pressure in the vacuum chamber was pumped down to below 5 Pa using a mechanical pump. The molecular pump and each gas path valve were opened to evacuate to 10 -4 Order of magnitude. In a mixed atmosphere of 200 sccmAr and 50 sccmH2, the system is heated at 200Pa for 50min to the target temperature of 850℃, and the distance between the upper and lower plates is fixed to 2.5cm. This is a heating process and no graphene growth is performed. After reaching the target temperature, the Ar and H2 gas flows are adjusted to 50sccm and 20sccm respectively, and the system pressure is maintained at 50Pa. When the gas flow is stable, the RF power supply is turned on and the power is set to 50w for 1min of etching. Finally, 3sccm of 5% CH4 is immediately introduced for graphene growth. The growth time is 30min. After obtaining a single layer of graphene that completely covers the copper foil, the RF power supply, CH4 flowmeter, H2 flowmeter and heating power supply are turned off, and the Ar flow rate is increased to 500sccm. The temperature is quickly cooled to room temperature. After it drops to room temperature, the Ar flowmeter is turned off.

[0066] S1-2: The substrate material on which the single-layer graphene is grown in step S1-1 is transferred into the thermal evaporation chamber through the operation control system, and copper is plated on the surface of the single-layer graphene to obtain a Cu / Gr / Cu layered structure foil. First, start the mechanical pump to pump the pressure in the vacuum chamber to below 2 Pa, and turn on the molecular pump until the vacuum degree reaches 5.0×10 -4 Pa, turn on the thermal evaporation power supply, keep the evaporation current at 40-50A, and control the copper plating rate at The copper plating thickness is 50nm.

[0067] S1-1-1: The Cu / Gr / Cu composite foil after copper plating in step S1-2 is transferred into the RF-PECVD vacuum chamber through the operation control system. In a mixed atmosphere of 200sccmAr and 30sccmH2, the system is heated at 180Pa for 40min to the target temperature of 650℃, and the distance between the upper and lower plates is fixed to 2.5cm. At this time, it is a heating process, and graphene growth is not performed. After reaching the target temperature, the Ar and H2 gas flows are adjusted to 50sccm and 8sccm respectively, and the system pressure is maintained at 25Pa. When the gas flow is stable, the RF power supply is turned on and the power is set to 200w. Finally, 3sccm of CH4 with a concentration of 5% is immediately introduced for graphene growth, and the growth time is 15min. After obtaining a single-layer graphene completely covered with a copper film, the RF power supply, CH4 flowmeter, H2 flowmeter and heating power supply are turned off, and the Ar flow rate is increased to 500sccm, and the temperature is quickly cooled to room temperature. After it drops to room temperature, the Ar flowmeter is turned off.

[0068] S1-3: Step S1-1-1 and step S1-2 are repeated 24 times in an alternating manner, that is, thermal evaporation of copper and RF-PECVD on the single-layer graphene, and RF-PECVD growth of graphene on the copper-plated film are repeated 24 times to obtain a graphene-copper composite foil having a thickness of about 26.2 μm and a graphene content of 0.031%, wherein the 24 layers of copper-plated films and the 24 layers of single-layer graphene do not contain a copper base material of a Cu / Gr / Cu layered structure.

[0069] S2: stack 16 pieces of highly conductive graphene copper composite foils prepared in step S1 and then hot press them to prepare highly conductive graphene copper composite materials. That is, stack 16 pieces of graphene copper composite foils prepared in step S1-3 and put them into the graphite mold of the hot press furnace. Set the pressure parameter to 40Mpa, the temperature parameter to 900℃, the heating and pressure increase time to 40min, and the heat preservation and pressure holding time to 40min. Turn on the mechanical pump to evacuate. When the pressure in the hot press furnace is lower than 10Pa, turn on the vacuum pump and evacuate to 1×10 -3 Pa. Turn on the heating power supply for hot pressing sintering. After the hot pressing is completed, turn off the heating power supply and cool naturally to room temperature, turn off the molecular pump and mechanical pump, open the vent valve, and open the cavity for sampling.

[0070] The CH4 is diluted with Ar.

[0071] The electrical conductivity of the graphene-copper composite was measured to be 128% IACS using the van der Pauw method.

[0072] In summary, RF-PECVD is used to deposit a single layer of graphene on copper. The free radicals generated in the plasma greatly reduce the energy barrier of the graphene nucleation and growth process, and reduce the overall heat budget by shortening the growth time and lowering the growth temperature, thus avoiding the evaporation of copper. Secondly, a copper film is plated on the surface of graphene by thermal evaporation to obtain a Cu / Gr / Cu foil. When the thickness of the foil is fixed, the graphene content in the composite material can be controlled by changing the thickness of the copper plating layer, and a highly conductive graphene copper composite foil with different graphene contents can be obtained. Hot pressing of the graphene copper composite foil stack can enhance the interface bonding of graphene and copper, and obtain a graphene copper composite material with a conductivity of up to 110%-130% IACS.

[0073] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be within the scope of protection of the present invention.

Claims

1. A method for preparing a highly conductive graphene copper composite material based on an in-situ co-deposition method, characterized in that: The following steps are included: S1: Preparation of highly conductive graphene copper composite foil by in-situ co-deposition method; S2: laminating and hot pressing a plurality of highly conductive graphene copper composite foils prepared in step S1 to prepare a highly conductive graphene copper composite material.

2. The method for preparing a highly conductive graphene copper composite material based on an in-situ co-deposition method according to claim 1, characterized in that: The step S1 includes the following steps: S1-1: In the radio frequency plasma chemical vapor deposition (RF-PECVD) system of the in-situ nano-laminated superstructure electrode material deposition equipment, a mixed atmosphere of Ar, H2 and CH4 is created. In this environment, a single layer of graphene is deposited on the surface of commercial high-purity copper foil using RF-PECVD; S1-2: transferring the copper foil on which the single-layer graphene is deposited into a thermal evaporation system, and thermally evaporating a layer of copper film on the surface of the single-layer graphene; S1-3: Repeat steps S1-1 and S1-2 alternately for multiple times to obtain a highly conductive graphene copper composite foil.

3. The method for preparing a highly conductive graphene copper composite material based on an in-situ co-deposition method according to claim 2, characterized in that: In the step S1-1, the commercial high-purity copper foil has a thickness of 25 μm; the RF plasma power is 50-300 W, the growth temperature is 650-900° C., the H2 flow rate is 5-20 sccm, the CH4 flow rate is 1-5 sccm, and the growth time is 10-30 min.

4. The method for preparing a highly conductive graphene copper composite material based on an in-situ co-deposition method according to claim 2, characterized in that: The commercial high-purity copper foil used in step S1-1 needs to be pretreated. The commercial high-purity copper foil is ultrasonically cleaned in hydrochloric acid, acetone, and isopropanol for 5 minutes in sequence to remove organic matter and oxide layer on its surface, and then blown dry with flowing N2; then placed in the polishing liquid, electrochemically polished for 30 minutes using a voltage of 2V, and then rinsed with deionized water for 5 minutes to wash away the polishing liquid remaining on the surface, and then blown dry with N2.

5. The method for preparing a highly conductive graphene copper composite material based on an in-situ co-deposition method according to claim 4, characterized in that: The mass fraction of the hydrochloric acid is 5%.

6. The method for preparing a highly conductive graphene copper composite material based on an in-situ co-deposition method according to claim 4, characterized in that: The polishing liquid is prepared by mixing phosphoric acid and ethylene glycol in a volume ratio of 3:

1.

7. The method for preparing a highly conductive graphene copper composite material based on an in-situ co-deposition method according to claim 2, characterized in that: The thickness of the thermally evaporated copper film in step S1-2 is 50-200 nm.

8. The method for preparing a highly conductive graphene copper composite material based on an in-situ co-deposition method according to claim 2, characterized in that: The thickness of the highly conductive graphene copper composite foil prepared in step S1-3 is 26.2 μm.

9. The method for preparing a highly conductive graphene copper composite material based on an in-situ co-deposition method according to claim 1 or 2, characterized in that: In the step S2, 16 sheets of highly conductive graphene copper composite foil are laminated and hot pressed; the hot pressing pressure is 40 MPa, the hot pressing temperature is 900° C., and the hot pressing sintering time is 40 min.

Citation Information

Patent Citations

  • Vertical graphene composite heat-conducting copper foil and preparation method thereof

    CN112853324A

  • Composite copper foil structure, preparation method thereof, copper-clad laminate and printed circuit board

    CN113873750A

  • Preparation method of graphene / copper composite material combining physical vapor deposition and chemical vapor deposition

    CN114959697A

  • Graphene copper-based composite material and preparation method thereof

    CN118241201A

Cited By

  • Preparation method of defective graphene field emission cold cathode

    CN115058704A

  • Graphene-copper co-deposition device

    CN120625046A

  • Graphene / copper composite film layer-by-layer stacked high-conductivity copper film and preparation method and application thereof

    CN120625047A

  • High-conductivity graphene / copper composite material and preparation method thereof

    CN122164903A